Analysis of the effectiveness of government policy at the local, provincial and regional levels on enabling environment for smallholder farmers in agribusiness supply chains in regions of South Sulawesi, Indonesia - Ferdi (2017)
Developing competitive agro-industries is essential to meet the growing demand for value-added agricultural products. The objective in this study is to analyse the effects of development policy at the local, provincial and regional levels to enhance the enabling environment for agribusiness supply chains in the region of South Sulawesi, Indonesia. This study resulted the model for the government to create an effective program and policy intervention to enhance the enabling environment at the micro level.